2018
DOI: 10.1002/ddr.21475
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral compound screening, peptide designing, and protein network construction of influenza a virus (strain a/Puerto Rico/8/1934 H1N1)

Abstract: Plant‐based antiviral therapy is the current need for holistic health care management, which can be achieved through screening of phytochemicals and designing of antiviral peptides. There exist certain host's factors which are directly involved for rapid viral replication causing worldwide pandemic. A total of 177 phytochemicals from Ocimum sanctum (L.), Tinospora cordifolia (Thunb.) Miers, Cinnamomum camphora (L.) J. Presl., Allium sativum (L.), Curcuma longa (L.), and Aloe vera (L.) Burm. f. were evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Also the currently available antiviral drugs (both approved and in clinical trials) are reported to have limited efficacy against SARS-CoV-2. 2,4,5 Hence there is an urgent need for identifying effective antiviral drugs against SARS-CoV-2. 6 Natural products have been viable and sustainable source of antimicrobial agents in the past and several natural compounds are reported to have antiviral properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the currently available antiviral drugs (both approved and in clinical trials) are reported to have limited efficacy against SARS-CoV-2. 2,4,5 Hence there is an urgent need for identifying effective antiviral drugs against SARS-CoV-2. 6 Natural products have been viable and sustainable source of antimicrobial agents in the past and several natural compounds are reported to have antiviral properties.…”
Section: Introductionmentioning
confidence: 99%
“…6 Natural products have been viable and sustainable source of antimicrobial agents in the past and several natural compounds are reported to have antiviral properties. 5,[7][8][9] Recently we have shown the efficacy of neem and tulsi based natural compounds against the key SARS-CoV-2 targets. 10 Tinospora cordifolia (TC), a deciduous, extensively-spreading, climbing her baceous vine of the family Menispermaceae is considered an essential herbal plant in the Indian system of medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The natural compounds from Tinospora cordifolia tested in this study showed therapeutically feasible efficacy against SARS-CoV-2 targets involved in attachment of the virus to host receptor (6VSB, 6M0J) and its replication (6M71, 6Y84). Although antiviral properties of Tinospora cordifolia has been reported before against H1N1 and Chikungunya Virus, [5,17,18] .27, 33.39±1.57, 66.79±3.14) against 6VSB was either similar or inferior to the natural compounds from Tinospora cordifolia. [6,10] 6VSB and 6M0J are responsible for viral attachment, while 6Y84 (main Protease) and 6M71 (RNA dependent RNA polymerase) are involved in viral replication.…”
Section: Discussionmentioning
confidence: 75%
“…[6] Natural products have been viable and sustainable source of antimicrobial agents in the past and several natural compounds are reported to have antiviral properties. [5,[7][8][9] Recently we have shown the efficacy of neem and tulsi based natural compounds against the key SARS-CoV-2 targets. [10] Tinospora cordifolia (TC), a deciduous, extensively-spreading, climbing herbaceous vine of the family Menispermaceae is considered an essential herbal plant in the Indian system of medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation